PROCESS TYPES IN STUDENTSâ€™ NARRATIVE TEXT - Erwin Oktoma (Indonesian EFL Journal, 2017)
This study aims to investigate the process type in studentsâ€™ narrative text. It involves 20 first grader of Department of English Education, University of Kuningan. The title of narrative text given to all respondents is â€œRabbit and Twenty Crocodiles.â€ This study raises two problems: the process types appear in students narrative texts and the errors of the process types occur in studentsâ€™ narrative texts. This research used a descriptive qualitative method to describe the data. As result, by using Derewianka (2002), the process types found in studentsâ€™ narrative texts were material, mental, verbal, and relational process. Material process was the dominant type found in studentsâ€™ narrative texts in which there were 232 material processes from 371 data with percentage 62.53%. It means that, in the text telling about a sequence of happenings and experiences, the characters did many material activities than the other process types. Besides, this research also found three process type errors occurred in studentsâ€™ narrative texts, namely material, verbal, and relational process. Material process is the dominant error occurred in studentsâ€™ narrative texts in which 100 errors occurred in 157 data with percentage 63,7%. In conclusion, considering that students face diffuculties mostly in material process, teacher should deal with its teaching more cautiously. Â Keywords: narrative text, transitivity and error, process types